Evidence Behind Upper Instrumented Vertebra Selection in Adolescent Idiopathic Scoliosis: A Systematic and Critical Analysis Review. Issue 9 (September 2021) - Baghdadi, Soroush; Cahill, Patrick; Anari, Jason; Flynn, John M.; Upasani, Vidyadhar; Bachmann, Keith; Jain, Amit; Baldwin, Keith
Abstract : Level selection is often a dilemma in adolescent idiopathic scoliosis (AIS) surgery. The goals of selection of the upper instrumented vertebra (UIV) are to achieve the most optimal proximal balance of the shoulders, minimize any caudal problems due to proximal imbalance, and promote optimal sagittal balance. Several authors have proposed guidelines for selection of fusion levels in AIS. These guidelines are mostly expert opinions of distinguished surgeons in the field; they are not derived from clinical trials but rather from clinical acumen and many years of experience. We have systematically reviewed and critically analyzed the literature regarding UIV level selection in AIS surgery. The guidelines outlined by experienced surgeons seem to be supported by mixed or low-level evidence. Moreover, variation in studies may be due to lower levels of evidence and/or data that were insufficiently controlled for bias, confounding factors, and chance.